2009
DOI: 10.1111/j.1471-0528.2009.02147.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimating intrapartum‐related perinatal mortality rates for booked home births: when the ‘best’ available data are not good enough

Abstract: Objective To critically appraise a recent study on the safety of home birth (Mori R, Dougherty M, Whittle M. BJOG 2008;115:554) and assess its contribution to the debate about risks and benefits of planned home birth for women at low risk of complications.Design Critical appraisal of a published paper.Setting England and Wales. Methods Six members of a multidisciplinary group appraised the paper independently. Comments were collated and synthesised.Main outcome measures Assessment of: overall methodology; assu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 21 publications
0
26
0
1
Order By: Relevance
“…The authors emphasised that the results should be interpreted with caution because of inconsistencies in the recorded data [30]. A critical appraisal found weaknesses in the study design and that estimates of risk were inaccurate [31]. Evers et al found an increased risk for perinatal death in women referred from midwifery care to obstetric care during labour in Utrecht in the Netherlands [32].…”
Section: Discussionmentioning
confidence: 99%
“…The authors emphasised that the results should be interpreted with caution because of inconsistencies in the recorded data [30]. A critical appraisal found weaknesses in the study design and that estimates of risk were inaccurate [31]. Evers et al found an increased risk for perinatal death in women referred from midwifery care to obstetric care during labour in Utrecht in the Netherlands [32].…”
Section: Discussionmentioning
confidence: 99%
“…Genel olarak bu çalışmalar, planlanan hastane doğumuna kıyasla, evde doğumun, azalmış sezaryen ve müdahaleli doğum oranları ve benzer maternal ve perinatal morbidite ve mortalite oranları ile ilişkili olduğunu bildirmiştir. Bununla birlikte, sistematik analiz için mevcut nüfus verilerinin kalitesinde ve bazı olgularda, araştırmaların metodolojik kalitesinde önemli sınırlamalar vardır (19) . Güney Avustralya'da yapılan bir araştırmada, evde doğumun, çok yüksek oranda intrapartum fetal ölümle (hipoksiye bağlı) ilişkili olduğu rapor edilmiştir (20) .…”
Section: Discussionunclassified
“…These findings raise the notion of the intrapartum-related perinatal mortality rate, which excludes deaths caused by factors such as prematurity and congenital anomalies (45). Unfortunately, reliable estimates of this potentially valuable measure are currently unavailable (46). Among nonanomalous fetuses, the home birth PMR exceeded the hospital birth PMR by 1.0 to 2.0/1000.…”
Section: Home Birth Outcomes and Safetymentioning
confidence: 95%